FIGURATIVE LANGUAGE IN SONG LYRICS BY RIHANNA AND KATY PERRY - Ni Komang Putu Mulya Sadiasih; Putu Chrisma Dewi (LITERA : Jurnal Bahasa Dan Sastra, 2016)
ABSTRACTSong is expression of the composer poured into the word or lyric and accompanied by musicarrangement. The combination between lyric and music are important to get good responses fromthe listener. The aims of this study are to identify and to analysesthe figurative language andsignificance concept in foursong lyrics of Rihanna and Katy Perry.The songs are Roar (2013),E.T. (2010) by Katy Perry and Diamond (2012), Only Girl (In The World) (2011) byRihanna.This is a qualitative research by the use of documentation method, such as record andtaking a note in each song lyrics. Knickerbocker and Reningger theory (1963) is used to identifythe data in this study. This study shows that six types of figurative language were found, namelyhyperbole, simile and metaphor in Rihanna song lyrics and hyperbole, simile, paradoks,metaphor, personification and irony in Katy Perry song. The use of figurative language asstandard significance has an important rule to express feeling of the composer and singer evenlistener.Keywords: figurative language, significance, song lyricsABSTRAKLagu adalah ekspresi komposer yang dituangkan ke dalam kata atau lirik dan disertaipengaturan musik. Kombinasi antara lirik dan musik penting untuk mendapat tanggapan baikdari pendengar. Tujuan dari penelitian ini adalah untuk mengidentifikasi dan menganalisiskonsep figuratif dan konsep signifikansi dalam lirik foursong dari lagu Rihanna dan Katy Perry.Lagu Roar (2013), E.T. (2010) oleh Katy Perry dan Diamond (2012), Only Girl (In The World)(2011) oleh Rihanna. Ini adalah penelitian kualitatif dengan menggunakan metode dokumentasi,seperti merekam dan mencatat dalam setiap lirik lagu. Teori Knickerbocker dan Reningger(1963) digunakan untuk mengidentifikasi data dalam penelitian ini. Studi ini menunjukkanbahwa enam jenis bahasa kiasan ditemukan, yaitu hiperbola, simile dan metafora dalam liriklagu Rihanna dan hiperbola, simile, paradoks, metafora, personifikasi dan ironi dalam laguKaty Perry. Penggunaan bahasa kiasan sebagai standar penting memiliki aturan penting untukmengungkapkan perasaan komposer dan penyanyi bahkan pendengar.Kata kunci: bahasa kiasan, signifikansi, lirik lagu